Status of sheep and goat farming in Lagkada Province of Thessalonika prefecture, in Central Macedonia, Greece - Katanos J.; Karabalis K.; Papadopoulou S. (Nutritional and foraging ecology of sheep and goats, 2009)
Lagkada Province of Thessalonika prefecture is located in Central Macedonia-Greece. In this region, 103,943 sheep and 100,281 goats are farmed. The total number of sheep and goat farms is 898. The number of sheep farms, goat farms and mixed farms with sheep and goat are 278, 357 and 263 respectively. With regard to the farm size 12.9, 23.6, 26.5, 31.8 and 5.2% of farms have got less than 100 animals, 101-200, 201-300, 301-500 and more than 500 animals respectively. The diet of sheep and goats in this region is based on pasture grass for the bigger part of the year. One month before the lambing and kidding and during the first 4-5 months of lactation, animals are supplemented with alfalfa hay and a concentrate based on cereals. Sixty sheep and goat farms of the province were surveyed. Results of the survey showed that with regard to the breed structure 8.3% of farms rear animals of the Chios breed, 50.0% possess crossbreds between local breed sheep and the Chios breed, while 41.7% have crossbreds between local breed sheep and a cross between Chios ewes and Friesian rams. For goat farms 5.9% of these have Saanen breed, 17.7% have crossbreds between the local Greek goat and imported breeds (i.e. Saanen, Alpine and Damascus) and 76.4% are breeding goats of the local Greek breed. 71.7% of farms derive from heritage, while 28.3% derived from a gradual development by farmers. With regard to the farmer's age structure, 13.3% of them are under 30 years old, 18.4% are between 31 and 45 years, 55.0% are between 46 and 60 and 13.3% are above 60. 6.7% of farmers did not achieve an elementary school certificate and 56.7%, 33.3 and 3.3 of farmers have an elementary school certificate, a secondary school certificate and a high school certificate respectively. As for the future of sheep-goat farms in the region, according to the farmers' answers, 45.0% of them will continue their profession, 23.3% will sell their animals, while 31.7% will continue through a family successor(s). With regard to farm size the study showed that 6.6, 30.0, 31.7, 21.7 and 10.0% of farms possess respectively less than 100 animals, 101-200, 201-300, 301-500 and more than 500 animals. As far as the land use is concerned in 25.0, 6.7, 48.3, 20% of cases, land is respectively privately-owned, only leased, community provided, and privately-owned and leased land. Finally, as far as the average milk yield (in kg milk/animal/year) is concerned, the study showed that 6.7% of farms produce 111-130 kg, 55.0% produce 131-150 kg and 38.3% produce above 150 kg.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)